Anammox enrichment culture has unexpected capabilities to biotransform azole contaminants of emerging concern. (February 2021) - Lakhey, Nivrutti; Sierra-Alvarez, Reyes; Couger, Matthew Brian; Krzmarzick, Mark J.; Field, Jim A.
Abstract: Azoles are contaminants of emerging concern. They have a ubiquitous presence in the environment due to their wide variety of uses. This study investigated the fate of two commonly occurring azole compounds in an anammox enrichment culture. The results showed that 1H-pyrazole (PA) and 1H-1, 2, 4-triazole (TA) were biotransformed yielding major biotransformation products, 3-amino-1H-pyrazole and 3-amino-1H-1, 2, 4-triazole, respectively. Nitrate and glucose greatly stimulated the biotransformation. Under optimized conditions, 80.7% of PA and 16.4% of TA were biotransformed in an incubation period of 6 days. High molar product yield of 84.5% and 83.6% was observed per mole of PA and TA biotransformed, respectively. This novel and selective biotransformation constitutes the first report on the microbial biotransformation of PA and is amongst the very few reports on the biotransformation of TA. This study also provides evidence that anammox enrichments have unexpected capabilities to biotransform organic contaminants of emerging concern. Graphical abstract: Image 1 Highlights: Biotransformation of azoles occurred in an anammox enrichment culture. Significant biotransformation of pyrazole and triazole occurred in 6 days. Nitrate and glucose promoted the biotransformation process. 3-amino-pyrazole and 3-amino-triazole were the biotransformation products. High molar product yields were observed for both biotransformation products.